Chemical Heritage Foundation Conversazione - Chemical Heritage Foundation (2000)
A panel discussion about the past and future of the chemical industry, held in 2000 as part of the opening of the Chemical Heritage Foundation's new facilities in Philadelphia. Introductory remarks are given by Arnold Thackray, President and CEO of the Chemical Heritage Foundation, DuPont CEO Charles Holliday, and Dow Chemical CEO and President, William Stavropoulos. The moderator for the conversation is Air Products and Chemicals' CEO, Harold "Hap" Wagner. Panelists are all chemical industry leaders: Dexter Baker of Air Products and Chemicals; Stuart Churchill professor of Chemical Engineering at the University of Pennsylvania; David Bryant of Union Carbide; Edith M. Flanigen of Union Carbide; John Johnstone of the Olin Corporation; John Sinfelt of Standard Oil/ExxonMobil; and Lewis Hagis of Atofina Chemicals. The majority of the discussion is about science education. This VHS tape is a "window dub": a version of a video recording which includes a running time code, provided to clients by a videographer.
Keywords: Chemical Heritage Foundation; Chemical industry; Thackray, Arnold, 1939-; Churchill, Stuart Winston, 1920-; Baker, Dexter F.; Holliday, Charles; Stavropoulos, William Spyros, 1939-; Bryant, David R., 1936-; Johnstone, John W., 1932-2011; Sinfelt, John H.; Terrorism; Science--Study and teaching